Pengaruh Agresivitas Pajak dan Media Exposure Terhadap Corporate Social Responsibility Dengan Ukuran Perusahaan Sebagai Moderasi - Siti Rohmah; Rahma Wiyanti; Andi Martias (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the impact of tax aggressiveness and media exposure on corporate social responsibility (CSR), with company size serving as a moderating factor. Tax aggressiveness and media exposure are the independent variables, while CSR is the dependent variable. Additionally, this research investigates whether company size can either strengthen or weaken the effects of tax aggressiveness and media exposure on CSR. The study sample consists of food and beverage companies listed on the Indonesia Stock Exchange from 2018 to 2022, totaling 18 companies observed over five years. Using purposive sampling, the final sample size is 90 observations. Hypotheses are tested using multiple regression analysis and Moderated Regression Analysis (MRA). The findings reveal that tax aggressiveness influences CSR, while media exposure does not. Furthermore, company size does not moderate the relationship between tax aggressiveness and CSR or between media exposure and CSR.